PERAN SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG KREATIF LAPANGAN DI PASAR INPRES MANONDA KOTA PALU - Ayu, Putri; Suasa; Samsu, M. Kafrawi Al-Kafiah (JPS: Journal of Publicness Studies, 2025)
The aim of this research is to find out the extent of the role of the Civil Service Police Unit in controlling Creative Field Traders at the Manonda Inpres Market, Palu City. The basis of this research is descriptive qualitative. Data and material collection was carried out through observation, interviews and documentation. Interviews were conducted with 8 informants. The location of this research is at the Civil Service Police Unit Office and Manonda Inpres Market, Palu City. This research uses Sutarto's theory which includes: (1) Role Conceptions, (2) Role Expectations, (3) Role Implementation. The data analysis used in this research is Miles, Huberman and Saldana, including data collection, data condensation, data presentation and drawing conclusions. The results of this research show that the role of the Civil Service Police Unit in controlling Creative Field Traders at the Manonda Inpres Market, Palu City has not been fully implemented well, which can be seen from 1 aspect that is implemented well and 2 aspects that are not implemented well starting from the Civil Service Police Unit have carried out control of the Creative Field Traders in accordance with the concept they prepared to carry out the control. It is the hope of the Civil Service Police Unit that Creative Field Traders comply with the applicable rules and regulations. The implementation of control is not yet running optimally because there are Creative Field Traders who are still violating existing rules and this has resulted in the expectations and implementation of control by the Civil Service Police Unit not going well.